2021
DOI: 10.2991/ijcis.d.210503.001
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation Algorithm Based on Knowledge Graph to Propagate User Preference

Abstract: In recommendation algorithms, data sparsity and cold start problems are inevitable. To solve such problems, researchers apply auxiliary information to recommendation algorithms, mine users' historical records to obtain more potential information, and then improve recommendation performance. In this paper, ST_RippleNet, a model that combines knowledge graphs with deep learning, is proposed. This model starts by building the required knowledge graph. Then, the potential interest of users is mined through the kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Knowledge graphs helped the model learn the needs and interests of consumers to provide personalized experience to them. According to the test results, this new method can provide better recommendations of movies, books or music [ 8 ]. Liang and Yin found that there is a poor balance of recommended resources and low trustworthiness of recommended content in traditional sports network multimedia teaching platform system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge graphs helped the model learn the needs and interests of consumers to provide personalized experience to them. According to the test results, this new method can provide better recommendations of movies, books or music [ 8 ]. Liang and Yin found that there is a poor balance of recommended resources and low trustworthiness of recommended content in traditional sports network multimedia teaching platform system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is assumed, there are a total of five pieces of music in the database, the candidate item sets obtained from scanning will contain five items. Moreover, the support of each item is computed [12]:…”
Section: A Music Recommendation Algorithm Based On Associationmentioning
confidence: 99%
“…The RippleNet model uses the user's historical preferences as a seed set and iteratively calculates the interest set of the first k neighborhood through the meta-paths in the knowledge graph to achieve the simulation of the user's interest propagation. The inputs to the model are user u and item v output is the predicted probability of that user clicking on item v [30].…”
Section: Step2 Calculate the Initial Similarity Between Clustersmentioning
confidence: 99%